PENDIDIKAN KARAKTER MENURUT AL-GHAZALI DAN RELEVANSI TERHADAP KARAKTER GEN-Z - Widya Putri, Nur Aliya; Zayas Farista, Zayas Farista; Muhammad Riswanda Kurniawan, Muhammad Riswanda Kurniawan; muhamaad wawan permana, Muhammad wawan permana (Al-Iqro', 2025)
This research is motivated by the author's curiosity about character education which has not been fully understood by students and has not been fully used as the main guideline and has not been fully implemented in the world of education in Indonesia, especially character education according to Imam Ghazali in the book Ayyuhal-Walad. The purpose of this study is to explain. (1) character education in general. (2) character education according to Al-Ghazali. (4) Gen-Z character education and (5) the relevance of character education according to Al-Ghazali with Gen-Z character education in the era of Globalization. This research is a library research, with the object of research being the book Ayyuhal-Walad and supported by several other books. The research approach used is a philosophical approach. While data analysis uses content analysis. The focus of the study discussed in this study is the concept of character education according to al-Ghazali in the book Ayyuhal-Walad